Association between biomarkers of tobacco consumption and lung cancer risk among daily smokers. Issue 2 (1st February 2022) - González-Marrón, Adrián; Martín-Sánchez, Juan Carlos; Pérez-Ortuño, Raúl; Fu, Marcela; Ballbè, Montse; Cartanyà-Hueso, Àurea; Matilla-Santander, Nuria; Pascual, José Antonio; Fernández, Esteve; Martínez-Sánchez, Jose M
ABSTRACT: Background: Biomarkers of tobacco consumption may play a role in the lung cancer risk assessment. However, the role of salivary biomarkers has not been well studied. The aim of this study is to assess the use of salivary biomarkers of tobacco consumption as lung cancer screening criterion. Research design and methods: Data came from the Determinants of cotinine phase 3 project (Barcelona, 2013–2014). We compared the concentrations of TSNAs, including NNAL, NNN and NNK, and cotinine, in saliva samples of 142 daily smokers from the general population according to their risk of lung cancer. High risk of lung cancer was defined as per the inclusion criteria in the US National Lung Screening Trial (NLST) and in the Dutch-Belgian lung cancer screening trial (NELSON). Results: Among daily smokers accomplishing the age criterion for lung cancer screening, salivary concentrations of cotinine, NNAL and NNK adjusted for sex were significantly higher (p-value < 0.05) in daily smokers at high risk of lung cancer compared to smokers not at high risk according to both NELSON and NLST criteria. Conclusions: Saliva concentrations of cotinine, NNAL and NNK may be used as additional criteria for lung cancer screening. Further research on this topic is guaranteed.